Analysis of thermodynamic parameters of glass forming metallic melts - Mishra R.K.; Dubey K.S. (My University, 2025)
The temperature dependence of the Gibbs free energy difference (ΔG) between the undercooled liquid and the corresponding equilibrium solid has been analysed for metallic glass forming systems in the frame of the expression obtained by expanding free energies of the undercooled liquid and solid phases in the form of Taylor's series expansion. The enthalpy difference (ΔH) and the entropy difference (ΔS) between the undercooled liquid and solid phases have also been analysed. The study is made for five different metallic glass forming materials, Au77Ge13.6Si9.4, Au53.2Pb27.5Sb19.3, Au81.4Si18.6, Mg85.5Cu14.5 and Mg81.6Ga18.4 and a very good agreement is found between calculated and experimental values of ΔG. The ideal glass transition temperature (Tk) and the residual entropy (ΔSR) of these materials have also been studied due to their important role in assigning the glass formation ability of materials. © 1997 Akadémiai Kiadó.